Modeling the evolution of inter-hospital referral networks: an agent-based modeling approach - Yang, Tao; Fan , Jie; Gu , Wenbin; Qin , Jing; Deng , Bing; Zhao , Xing; Deng , Wenwen; Wang , Wei (Frontiers in Physics, 2025)
IntroductionIn many countries, especially large developing nations like China, hierarchical healthcare systems face persistent structural challenges such as unbalanced resource allocation and inefficient referral networks. To capture the impact of individual behavior on the evolution of healthcare system structures, this study develops an agent-based modeling (ABM) approach to simulate the dynamic formation of inter-hospital referral networks.MethodsThe model introduces a strategic game-theoretic mechanism among patients, where each agent makes referral decisions based on multiple factors, including medical benefits, commuting costs, and limited information, under resource constraints. Through these decentralized decisions, a directed and weighted referral network emerges, reflecting realistic behavioral patterns. Based on the simulated network, topological analysis is performed to identify key hospitals and design targeted resource allocation strategies.ResultsWe simulate the dynamic formation process and obtain a stable referral network structure. The results show that tertiary hospitals exhibit high centrality, indicating a structural “Matthew effect.” Furthermore, the observed community division pattern may correspond to actual administrative regions or the organizational frameworks of medical alliances. In addition, compared to simply strengthening core hospitals, the referral bottleneck mitigation strategy can reduce patient loss while decreasing the overall referral frequency within the system.DiscussionThe study reveals structural imbalances in China's referral network, characterized by a “siphoning effect” toward tertiary hospitals and underutilized secondary institutions. Our findings demonstrate that bottleneck mitigation strategies outperform core-hospital strengthening in reducing both patient loss and referral frequency. To address these issues, we propose a multi-level reform framework encompassing operational capacity-building, institutional payment reforms, and strategic medical consortium optimization. This integrated approach aims to transform the top-heavy healthcare structure into an efficient, hierarchical system with equitable resource distribution.